The Effect Of Big Book Learning Media On Reading Literacy Abilities Of Grade Iv Students At Rade Elementary School - Astuti, Elsa; Nursa’ban, Eva; Yuningsih RS, Yuyun (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to determine the effect of using Big Book media on the reading literacy skills of fourth-grade students at Rade Elementary School. Observations show that most students still read haltingly, less fluently, and get bored quickly during reading lessons. Observations in fourth-grade students at Rade Elementary School indicate that some students still face reading difficulties. Some students read haltingly, skip words, use incorrect intonation, and even do not understand the content of the reading after finishing reading. Differences in ability are also quite striking: some students are already fluent, but many are still in the low category. Low reading motivation is further exacerbated by minimal parental support and a lack of interesting reading materials at home. This condition causes some students to get bored quickly when reading lessons are conducted using conventional methods. This study used a quasi-experimental design with a pretest-posttest control group model, involving 40 students divided into an experimental group and a control group. The research instrument was a reading literacy test that covered aspects of reading comprehension, fluency, and reading accuracy. The results showed a significant increase in reading literacy skills in the experimental group. The average pretest score of 76.50 increased to 82.00 in the posttest. Based on the Wilcoxon test results, the use of Big Book media has proven effective in improving students' reading literacy skills. Therefore, Big Book can be used as an innovative and effective alternative learning medium for implementation in elementary schools.